Perchance to Dream: Architecture and the Conflict of Historical Perception - Basson, Steve (Society of Architectural Historians, Australia and New Zealand, 2006)
For history, architecture remains both a property of the universal and trans-historical and subject of a unified and coherent structure of chronological progression. As part of this traditional and privileged framework of periodized and continuous succession, architecture has retained for itself an historical identity expressive of the eternal, romantic and heroic. But time has itself moved on, leaving behind what once constituted the certitudes of historical perception and analysis. The old objects of exemplification and origin have evaporated, the heroes have become mortal, continuity has surrendered to rupture, and the singular ideals of truth and reality fragmented. And yet, seemingly indifferent to the problems of the meta-historical and metaphysical, architecture persists along its own path of historicist discourse and through this, subsumes all acts and ends of built form to an order of undifferentiated motives and needs that transpose the events of the past into an illusory history of the same. Here, history becomes expressive of a dreamed reality and as a result, a terrain of critical contestation. The following discussion will consider this conflict in relation to the conventional perception and use of architecture's historical subject.